Tobacco Use, Dependence and Psychiatric Co-Morbidities Among Patients Admitted in Psychiatry Ward - Limbu, S; Shakya, DR; Sapkota, N; Gautam, R; Paudel, L (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Nicotine dependent individuals among the tobacco users are in greater risk of having tobacco related disease and psychiatric co-morbidities. There is little information about the tobacco use and nicotine dependence among psychiatric patients in developing countries including Nepal. This study was done to estimate the prevalence of tobacco use, the level of nicotine dependence among the users and the psychiatric disorder specific prevalence among tobacco users admitted in psychiatry ward. Material And Method: A cross-sectional study was conducted in In-patient setting of Department of Psychiatry, BPKIHS. Ninety cases (size) were enrolled. The Fagerström Test for Nicotine Dependence (FTND) was applied to assess the level of nicotine dependence and the Mini International Neuropsychiatric Interview (M.I.N.I.) for diagnosis of Psychiatric disorders. Results: The prevalence of tobacco use was 62.2%. Tobacco use was more common among males (p value< 0.05).Smokeless form was the commonest form of tobacco. Majority of tobacco users had moderate nicotine dependence and had started the use in adolescence and in their 20s. Psychotic disorders were the most common diagnosis among the admitted patients. Conclusion: Tobacco use is common in patients with psychiatric disorders. Nicotine dependence should be looked into for holistic management. Treatment approaches should be tailored in tobacco users with comorbid psychiatric disorders, as this specific population has high prevalence of tobacco use and higher nicotine dependence. J Psychiatrists’ Association of Nepal Vol. 6, No. 2, 2017, Page: 54-59